Governing the Responsible Pilgrim: Da’wah, Surveillance, and Islamic Governmentality in the Prevention of Illegal Hajj - Zain, Machsun; Aswadi; Fuad, Ahmad Nur (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
This study examines the mechanisms for preventing illegal hajj pilgrimages at the Ministry of Religious Affairs Regional Office in East Java through a Foucauldian governmentality framework. Using a qualitative case study methodology, data were collected through in-depth interviews with 15 ministry officials, direct observation of regulatory practices over 6 months, and documentary analysis of ministerial regulations, standard operating procedures, and enforcement records from 2023 to 2025. Data were systematically coded to identify governmental rationalities (e.g., risk management, spiritual welfare protection), technologies of power (e.g., registration databases, site inspections), and subject positions (e.g., "responsible pilgrim," "compliant travel agency"). Findings reveal three distinct governmentality modalities comprising disciplinary mechanisms through registration systems and surveillance, sovereign interventions via legal sanctions and permit revocations, and neoliberal techniques emphasizing self-regulation, operating not as separable analytical categories but as mutually constitutive tensions in which each modality conditions the effectiveness and limits of the others. Critically, the findings reveal that these governance mechanisms are constitutively implicated in reproducing the structural conditions of quota scarcity and extended waiting periods that generate illegal market demand in the first place. This study contributes to governmentality scholarship by demonstrating that the framework requires modification in Islamic bureaucratic governance contexts: pastoral rationalities here have not been secularized but Islamicized, collective religious obligation replaces liberal individualism as the normative anchor of subjectification, and the tripartite schema functions as an assemblage of productive tensions rather than a descriptive typology, extending the framework’s analytical purchase beyond the Western liberal democratic contexts in which it was originally developed.